FIGURE 22 in Morphological features of larvae of Pandalus eous, P. goniurus, and P. tridents (Decapoda, Pandalidae) from planktonic samples taken in marine waters near Kamchatka Peninsula - Sedova, Nina; Grigoriev, Sergey (Zenodo, 2017)
FIGURE 22. Morphology of antennae of P. goniurus (A, after Haynes, 1978) and P. eous (B, after Haynes, 1979). Scale: 0.5 mm.